The Relationship between Peer Social Support with The Resilience of Blind Adolescents in Surakarta - Anis Noviatun; Hermawan Hermawan; Mahardika Supratiwi (Journal of ICSAR, 2022)
This study aims to determine the relationship between peer social support with the resilience of blind adolescents in Surakarta. This research is included in the type of quantitative research with a correlational research design. The subjects in this study were 30 blind adolescents in Surakarta who were selected by purposive sampling technique. Data collection is done by distributing online scale. The instrument used in this study consisted of the Scale of Resilience of Blind Adolescents (α equals 0.900) and the Scale of Peer Social Support (α equals 0.846). The data were analyzed using simple linear regression analysis techniques with the significance level. equals 0.01. The results of data analysis obtained the value of tcount more than ttable is 3.504 more than 2.7632 with p equals 0.002 (p less than 0.01). Based on data analysis, it is also known that the correlation coefficient is 0. 552. The coefficient of determination (Rsquare) is 0.305 or the effective contribution of the predictor variable to the criterion variable is 30.5 percent. Based on these results it can be concluded that there is a significant relationship between peer social support and the resilience of blind adolescents in Surakarta. It means that if the social support of peers goes up, the resilience of blind adolescents goes up. Conversely, if the social support of peers goes down, then the resilience of blind teenagers also falls.